Una historia hecha de cartas. La serie documental « Cartas en el tiempo » de La 2 de TVE - Verónica Sierra Blas; Blanca Flaquer Carreras-Candi; Antonio Castillo Gómez; Nuria Barreiro Gómez (Amnis)
Between 2018 and 2019 the two seasons of the documentary series Cartas en el tiempo were shown in La 2 of TVE. Across a selection of letters conserved in different types of archives, written on diverse historic periods and by persons of different condition and class, the 24 episodes that composed it were useful for diffuse, with an original and entertaining format, the History of Spain to the public. Also, the series pretends to remark the value of the correspondence like historical source and to raise awareness about the importance of its familiar or personal conservation. This article wants to relate our work and experience, focused our attention on some letters produced in our recent History : Transition and Democracy periods. In addition, we will reflect on the impact of the program thanks to the audience rates and different information registered in our web page and our social networks.